TIPOLOGI KEPEMIMPINAN LEMBAGA PENDIDIKAN ISLAM - Faisal Daut; Hamka (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2021)
The article examines typology of leadership in Islamic education institution. It is particularly aimed to portray how the approach, models, and typologies construct leaderships in Islamic education institution. The article employs qualitatif interpretive paradigm which is fully based on the library research while content analysis is made use. The results of the study show that leadership is an action, activity of a person or leader to move, engage, influence, motivate other people/groups to achieve organizational goals. The study further shows that there are different types of leadership. First, the Ohio study of leadership stresses on the ability, skill, and level of influence that a person partakes from which he or she develops two dimensional leaderships: initiating structure and considerate. Second, the Michigan study of leadership concerns more on productivity of employees as the result of effective leadership. Third, the democratic leadership is in great demand in contemporary Islamic education institution because this type of leadership enables all stakeholders to prompt effective participations in an organization. To sum up, the article is expected to provide new insights for leaders in Islamic education institution to transform their leaderships to all stakeholders of the organization to achieve its ultimate goal.